STATUS OF PITUITARY-THYROID AXIS OF NEWBORNS AND ITS RELATIONSHIP WITH ANTHROPOMETRY AND MATERNAL FACTORS AT BIRTH - CHANDRIKA D NAYAK; MADHAVA KAMATH; DINESH M NAYAK; NAGESHA K.M (International Journal of Pharma and Bio Sciences, 2012)
Thyroid hormone is crucial for growth and hence the current study is designed to correlate the cord blood thyroid stimulating hormone (TSH) levels with their anthropometry and maternal factors in 187 newborns. Statistical analysis was done by Mann Whitney-U test and Spearman correlation coefficient. TSH levels were significantly higher in males than in female newborns (P=0.018). Low birth weight newborns had significantly lower TSH than normal or high birth weight newborns (P=0.02). Ponderal Index exhibited a significant negative correlation (P=0.012) whereas head circumference did not correlate with TSH. Relationship between maternal factors like age, parity and MOD and newborns’ TSH levels were statistically not significant. This study creates a hope for using TSH as a tool for screening various metabolic changes in newborns with different anthropometry.